2011
DOI: 10.1007/s11274-011-0678-6
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and physico-chemical characterization of exopolysaccharides produced by the cyanobacterium Oscillatoria formosa

Abstract: Exopolysaccharides of the cyanobacterium Oscillatoria formosa have been physico-chemically characterized and kinetics of their production studied. The organism produced 334.8 lg EPS per ml culture in 24 days with the maximum rate of production obtained during initial days of growth. HPLC analysis of the EPS hydrolysate revealed that besides three unidentified sugars, EPS contained ribose, mannose, and galacturonic acid. FT-IR spectrum of EPS revealed the presence of methyl, carboxyl and C-N groups. Elemental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…, Anabaena Singh and Das, 2011), Nostoc (Otero and Vincenzini, 2003;Otero and Vincenzini, 2004;Singh and Das, 2011) and Oscillatoria (Jindal, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…, Anabaena Singh and Das, 2011), Nostoc (Otero and Vincenzini, 2003;Otero and Vincenzini, 2004;Singh and Das, 2011) and Oscillatoria (Jindal, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Khattar et al [11] observed that viscosity of EPS of the cyanobacterium Limnothrix redekii was sensitive to temperature. On the other hand, in another study it was observed that viscosity of EPS of Oscillatoria formosa was insensitive to temperature [32]. Most foods are subjected to variations in temperature during production.…”
Section: Discussionmentioning
confidence: 96%
“…Ca6, Lactobacillus kefiranofaciens, Lactobacillus plantarum and Lactobacillus rhamnosus, can produce EPS [4,5,6,8,9]. The EPS produced by lactobacilli was an important functional compound for their survivals in hypertonic environment [29]. Reported lactobacilli with producing EPS were approximately 30 species [6].…”
Section: Discussionmentioning
confidence: 99%